ChemInform Abstract: Development and Sensing Applications of Fluorescent Motifs within the Mitochondrial Environment. Issue 49 (December 2015) - Roopa, Roopa; Kumar, Naresh; Bhalla, Vandana; Kumar, Manoj
Abstract: Review: 152 refs.